Perancangan Dan Rekomendasi Proses Bisnis Berbasis Teknologi Informasi Pada Pasar Tradisional Menggunakan Business Process Improvement (BPI) (Studi Kasus: Pasar Oro-Oro Dowo Malang) - Dimounitif Nelaspaba; Andi Reza Perdanakusuma; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Oro Oro Dowo Market Malang is one of the traditional markets with various kinds of commodities on sale by traders. Besides sales and purchase transaction services, other operational activities include Market Management services. However, there are problems such as not optimal results of the market retribution because there are traders who have not paid fees according to the nominal provisions in force, implementation of the e-retribution system is constrained by signals, and most of the market management activities are still not utilizing information technology. Therefore, evaluation is needed to find problems and improvements to solve problems. In this study, business processes are modeled by Business Process Modeling and Notation (BPMN), then business process evaluation with Failure Mode and Effect Analysis (FMEA) method and 5 Why's Analysis and recommendations for business process improvement using streamlining tools in the Business Process Improvement (BPI) method. Improvements were made to activities with the highest RPN value to focus on the urgency of the problem. Furthermore, simulation is carried out between the current business process (as-is) and the recommendation (to-be) to measure the effectiveness and efficiency of the improvement recommendations. The simulation results on the Market Retribution Withdrawal business process showed an increase in time efficiency of 24.8%. This can occur due to improvements made by changes and additional activities as well as the use of information systems.